Homologous recombination repair capacity in peripheral blood lymphocytes and breast cancer risk. (21st July 2020) - Shen, Jie; Song, Renduo; Chow, Wong-Ho; Zhao, Hua
Abstract: Deficiency in homologous recombination repair (HRR) capacity is frequently observed in breast tumors. However, whether HRR deficiency is a tumor-specific biomarker or a risk factor for breast cancer is unknown. In this two-stage study, using a host cell reactivation assay, we assessed the relationship between HRR capacity in peripheral blood lymphocytes (PBLs) and breast cancer risk. The discovery stage included 152 breast cancer patients and 152 healthy controls matched on age and race. HRR capacity was found to be significantly lower in Black women than in White women among controls ( P = 0.015) and cases ( P = 0.012). Among cases, triple negative breast cancer patients had significantly lower HRR capacity than ER+/PR+ breast cancer patients ( P = 0.006). In risk assessment, HRR capacity was found to be significantly lower in cases than in controls ( P < 0.001), and decreased HRR capacity was associated with 1.42-fold increased risk of breast cancer (95% CI: 1.21, 2.53). In the validation stage, we assessed HRR capacity in a nested case–control study using pre-diagnostic samples. We found that decreased HRR capacity was associated with 1.21-fold increased risk of breast cancer (95% CI: 1.04, 4.58). In summary, our results demonstrate that decreased HRR capacity in PBLs is a risk factor for breast cancer. Abstract : We found that deficiency of homologous recombination repair capacity is a risk factor for breast cancer.